Worldwide Extension Study - International Food Policy Research Institute; University of Illinois (International Food Policy Research Institute, 2019)
The “Worldwide Extension Study” effort was undertaken by the International Food Policy Research Institute, funded by the United States Agency for International Development and in collaboration with the University of Illinois, FAO, the Global Forum for Rural Advisory Services, and regional organizations including Inter-American Institute for Cooperation on Agriculture and the French Agricultural Research Centre for International Development. The objectives of the GFRAS study were to assess and provide empirical data on the current status of pluralistic extension systems worldwide for use in planning future efforts to modernize and strengthen these rural extensions and advisory services. The study focused on collecting useful empirical data on the human and financial resources of agricultural extension and advisory systems worldwide, as well as other important data and information, including: the primary extension service providers in each country (e.g. public, private and/or non-governmental organizations); which types and groups of farmers were the primary target groups (e.g. large, medium, and/or small-scale farmers, including rural women) for each extension organization; how each organization’s resources were allocated to key extension and advisory service functions; each organization’s information and communication technology resources and capacity; and what role, if any, different categories of farmers played in setting extension’s priorities and/or assessing performance.